Meningkatkan Kepuasan Nasabah di Era Digital: Peran User Experience dan Digital Sharia Compliance pada BYOND by BSI - Yusuf A; Juli Darma Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This studyaims to analyze the effect of user experience and digital marketing on customer satisfaction among users of the BYONd by BSI application in Kerinci Regency, Jambi Province. This study uses a quantitative approach, with primary data in the form of questionnaires distributed to 110 research respondents. The data in this study were processed using SEM PLS . 3 2024. The results of the study show that the User Experience variable has positive effect on customer satisfaction among users of the BYOND by BSI application, with a coefficient value of 0.208 and a t-statistic of 2.398 (> 1.96) or a p-value of 0.017 (< 0.05), which indicates a significant effect. Meanwhile, the Digital Sharia Compliance variable also has a positive effect on Customer Satisfaction, with a coefficient value of 0.119 and a t-statistic of 1.057 (> 1.96), so it can be concluded that compliance with sharia principles in digital services is not significant in increasing customer satisfaction.